Non-planar elliptic vertex - M. A. Bezuglov; A. I. Onishchenko (Journal of High Energy Physics, 2022)
Abstract We consider the problem of obtaining higher order in regularization parameter ε analytical results for master integrals with elliptics. The two commonly employed methods are provided by the use of differential equations and direct integration of parametric representations in terms of iterated integrals. Taking non-planar elliptic vertex as an example we show that in addition to two mentioned methods one can use analytical solution of differential equations in terms of power series. Moreover, in the last case it is possible to obtain the exact in ε results.